Forensic Toxicology : Principles and Concepts - Lappas, Nicholas T.; Lappas, Courtney M. (London: Academic Press, 2024)
The second edition of Forensic Toxicology: Principles and Concepts takes the reader back to the origins of forensic toxicology providing an overview of the largely unchanging principles of the discipline. The text focuses on the major tenets in forensic toxicology, including an introduction to the discipline, principles of forensic toxicology including pharmacokinetics, pharmacodynamics, drug interactions and toxicogenomics, fundamentals of forensic toxicology analysis, types of interpretations based on analytical forensic toxicology results, and reporting from the laboratory to the courtroom. Also included in the second edition is a Unit focused on the forensic toxicology of individual drugs of abuse.
Includes Glossary and index
Keywords: Forensic toxicology; Toxicology; Drugs$1 (BAnalysiss; Poisons$1 (BAnalysiss; Substance abuse$1 (BTestings; Forensic sciences